Occurrence of quinolones in cultured fish from Shandong Province, China and their health risk assessment. (July 2022) - Wang, Xiaolin; Jiao, Yanni; Wang, Guoling; Li, Fenghua; Shao, Lijun; Zheng, Fengjia; Wang, Lin; Chen, Fangfang; Yang, Luping
Abstract: The residue levels of 6 quinolones in 160 cultured fish samples from Shandong Province, China were investigated using UPLC-MS/MS. The detection rate was 43.1% and enrofloxacin had the highest detection rate as well as the highest residue concentration. The violation rates were 2.50% for the sum of enrofloxacin and ciprofloxacin and 1.25% for ofloxacin. Among the 9 fish species, quinolone contamination problems should receive more attention in Carp, Grass carp, Crucian and Catfish. The health risk assessment showed that when calculated by the maximum concentration, the estimated daily intakes (EDIs) of Carp, Grass carp and Crucian for the high consumption group accounted for more than 10% of the acceptable daily intakes (ADIs), indicating that a large intake of these fish species might pose a potential health risk and health risk monitoring of quinolones in cultured fish should be continually performed. Highlights: Quinolones are widely used in aquaculture in Shandong Province, China. Enrofloxacin has the highest detection rate and residue level. The quinolone residues in different fish species are analyzed and discussed. Large intake of Carp, Grass carp and Crucian might pose a potential health risk.